2011
DOI: 10.1007/s10096-010-1134-5
|View full text |Cite
|
Sign up to set email alerts
|

Specific humoral reaction of hemorrhagic fever with renal syndrome (HFRS) patients in China to recombinant nucleocapsid proteins from European hantaviruses

Abstract: Hemorrhagic fever with renal syndrome (HFRS) is endemic in East Asia and Europe. This study was initiated to investigate the reactivity of antibodies in sera of Chinese HFRS patients with the recombinant nucleocapsid proteins (rNPs) of Hantaan virus (HTNV), Dobrava-Belgrade virus (DOBV), and Puumala virus (PUUV), which are the prevalent hantavirus strains in Europe. Forty-eight pairs of acute and convalescent sera were collected from HFRS patients in Hubei, China (1985-2002) and tested by indirect IgG, IgA, an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
5
0

Year Published

2012
2012
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(6 citation statements)
references
References 28 publications
1
5
0
Order By: Relevance
“…Given the peak periods of HFRS identified in our seasonal analysis, we infer that HFRS was primarily caused by HTNV in the 1980's and 1990's. This is consistent with previous findings indicating that the majority of patients with HFRS are infected with HTNV [32]. However, during the last decade, the HFRS has begun to occur more frequently in the spring and summer, accounting for about 50% of all cases.…”
Section: Discussionsupporting
confidence: 93%
“…Given the peak periods of HFRS identified in our seasonal analysis, we infer that HFRS was primarily caused by HTNV in the 1980's and 1990's. This is consistent with previous findings indicating that the majority of patients with HFRS are infected with HTNV [32]. However, during the last decade, the HFRS has begun to occur more frequently in the spring and summer, accounting for about 50% of all cases.…”
Section: Discussionsupporting
confidence: 93%
“…Numerous studies have identified the N protein as highly conserved among orthohantaviruses, making it a valuable target for diagnosing and developing vaccine candidates [11]. Studies support this assumption; the reactivity of recombinant PUUV N proteins was demonstrated in HFRS convalescent samples [13]. It was reported that anti-N protein IgM was detected in the serum at the acute phase of infection, and IgG was detected in convalescent sera at greater levels.…”
Section: Introductionmentioning
confidence: 95%
“…Patients were recruited from 12 districts in Hubei Province, China and were unrelated. All patients were diagnosed during hospitalization from 1986 to 1995 according to standard clinical criteria (Xiong et al, 2011), which mainly include: age ≥ 14 years, febrile time ≤ 4 days, typical HFRS symptoms and signs (e.g., fever, proteinuria, hematuria), and potential exposure history to wild rodents or other HFRS patients. Patient sera were subsequently confirmed to be positive by indirect IgM/IgG enzyme-linked immunosorbent assays (ELISAs) performed in our laboratory, using mixed antigens of HTNV and SEOV.…”
Section: Study Participantsmentioning
confidence: 99%